The Influence of Financial Knowledge, Financial Attitude, Financial Behavior on the Growth of MSMEs with Financial Literacy as a Mediation Variable - Marissa, Sahda; Fitriyah, Fitriyah (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2023)
Small, Micro, and Medium Enterprises (MSMEs) play an important role in various economic activities globally. The success of an MSME depends on the manager or manager of the MSME. Financial literacy enables MSME managers and owners to decide well on the financial decisions that must be taken. This research aims to determine the influence of financial knowledge, financial attitudes, financial behavior, financial literacy on the growth of MSMEs. The sample for this research is MSMEs assisted by the Department of Cooperatives and Trade and Micro Enterprises in Trenggalek Regency which already has Business Identification Numbers for 91 MSMEs. The analysis tool used is PLS-SEM with WarPLS 8.0 software. The research results show that financial knowledge and financial attitudes do not influence the growth of MSMEs, while financial behavior and financial literacy influence the growth of MSMEs. Financial attitudes, financial knowledge, and financial behavior have a significant effect on financial literacy. Financial literacy is not able to mediate financial attitudes towards financial growth, financial literacy is able to mediate the relationship between financial knowledge and financial behavior towards the growth of MSMEs